Analysis of parental behaviors in relation to play and motor stimulation of their 1 to 4 years old children. An exploratory study (Agora for Physical Education and Sport, 2019)
Parental behaviors play a key role in the acquisition of habits and customs by their 1 to 4 years old children. This paper aims to explore children’s habits towards play and movement. To do so, we’ve used the Comprehensive Early Childhood Parenting Questionnaire (CECPAQ), specifically the items related to the domain of stimulation. Data suggest that particular parental behaviors tend to stimulate and favor children's play during those early ages; however, some differences have been found in relation to gender (favorable to children) and to the (higher) level of urbanization.
Keywords: Stimulation; toddler and preschool child; parental behaviors; development; game